The auditor's assessment of the ability of the economic unit on going concern at crises - Haider M. Rasheed; Wafaa A. Al-dabbass (Journal of Madenat Alelem University College, 2022)
This research stems from the importance of the process of measuring and assessing the auditor's ability to continue in an abnormal situation, which is the situation of crises and the negative aspects they reflect on the economic unit that may prevent it from being able to perform its operations and practice its activity even if its ability to achieve profits and benefits before the occurrence the crisis does not suffer economic unity of any potential faltering Mali, explains research how can the crisis be reflected on the unit's ability economic to continue the need for the auditor to make such an assessment and quickly depending on available information and performing procedures for additional access to audit evidence is based upon a mechanism to evaluate verifier unit economic capacity to continue under the crisis, the most important findings of her research is to use verifier prediction models stalled and the failure of the units of economic assisted in identifying over the possibility of taking units of economic activity and sustainability performance of their work or not, and appointed auditors in learning about MCSE al Units of economic to continue under the crisis hit the economic unit, either the most important recommendations was the need for attention to accounting standards board and verifiability local and international reference for the auditor to work evaluation of the examination of the ability of the units of economic to continue to perform its activities in the event of any crisis hit the perimeter of the economic unit, the necessary modules governmental instruct and procedures for dealing with crises that surround units, economic, threatened and makes them fail to achieve their goals and put an end to the end of the economic, the need for all institutions and government departments and their associations and other organizations and units of economic add a new section to a structure called "crisis management" who diagnoses each risk affects the Doing economic unitary work and preventing it from continuing to practice its activity No, the country does not live through crises that strike it from time to time.